Constructivist Approach to Language Learning: Linking Piaget's Theory to Modern Educational Practice - Lalu Idham Halid (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to explore the application of the constructivism approach in language learning by connecting Jean Piaget's theory of cognitive development with modern educational practices. Constructivism theory emphasizes that learning is an active process in which students build knowledge through experience and interaction with the environment. In the context of language learning, this approach is considered relevant to increase student engagement and support more meaningful learning. This study uses a qualitative approach with a case study design, involving in-depth interviews, classroom observations, and document analysis. Participants consisted of 10 teachers and 20 students who were selected by purposive sampling based on their experience in applying constructivist learning methods. The results show that the constructivism approach can increase students' active participation, improve critical thinking skills, and provide a more contextual and relevant language learning experience. Teachers who apply Piaget's principles, such as experiential learning, reflection, and collaboration, report increased student learning motivation. However, challenges in implementing this method include time constraints, a rigorous curriculum, and a lack of support resources for project-based learning. The study concludes that although constructivist approaches have great potential in language learning, further support is needed in terms of curriculum flexibility and resources. Recommendations for educators include increased use of technology and project-based teaching strategies to support more interactive and participatory language learning.